Gembala Adalah Tugas Yang Mulia - David Bunbunan Hasibuan (STT IKSM SANTOSA ASIH, 2024)
Abstract: Abstract: What will be achieved in this writing, First: provide an explanation of the duties and responsibilities of a congregational pastor. Second, a congregational pastor not only needs to know his calling as a pastor but also that the pastor has good spiritual standards. Thirdly, the duties and role of a congregational pastor have a big impact on the growth of the congregation's faith both in quality and quality. This research methodology uses qualitative methods.